Liturgical Participation: An Effective Hermeneutic for Individuals with Profound Memory Loss - Yogerst, Jared D. (Religions, 2021)
In non-pandemic times adults with profound memory loss (PML) are isolated by virtue of the effects of their decline. The marginalization of this cohort has been greatly exacerbated by the present pandemic. Individuals and their caretakers are not seen as active members, but as objects of pastoral care. Leaving individuals outside of the present moment, PML makes it difficult to communicate or function. They may behave in ways that would be antithetical to their thinking. Individuals were isolated from their homes and worshiping communities. In this paper I will present a liturgical hermeneutic of Liturgical Participation. I will illustrate its effectiveness as a catechetical methodology for individuals experiencing PML. The methodology of Liturgical Participation will aid ministers in the work of raising the consciousness of individuals as active participants in the work of God.